1996
DOI: 10.1177/030098589603300620
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan and Lesions in Genetically Heterogeneous (Four-way Cross) Mice: A New Model for Aging Research

Abstract: Abstract. Genetically heterogeneous animal models provide many advantages for research on aging but have been used infrequently. We present here lifespan and lesion data from a study of mice bred as a cross between (AKR/J x DBA/2J)F, females and (C57BL/6J x SJL/J)F, males. In such a four-way cross population, each mouse is genetically unique, but replicate populations of essentially similar genetic structure can be generated quickly, at low cost, and of arbitrary size from commercially available, genetically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…Likewise, the rate of change in luminescence activity at any age was not predictive of death (Figures 2F and S2H–S2J). Consistent with previous assessments of mortality in several strains of inbred as well as outbred mice (Chrisp et al, 1996; Miller et al, 2011; Wilkinson et al, 2012), all autopsied animals from the study showed signs of advanced cancer. Moreover, no significant decrease in median survival was observed between p16 +/+ and p16 +/LUC animals (Figure S2K).…”
Section: Resultssupporting
confidence: 86%
“…Likewise, the rate of change in luminescence activity at any age was not predictive of death (Figures 2F and S2H–S2J). Consistent with previous assessments of mortality in several strains of inbred as well as outbred mice (Chrisp et al, 1996; Miller et al, 2011; Wilkinson et al, 2012), all autopsied animals from the study showed signs of advanced cancer. Moreover, no significant decrease in median survival was observed between p16 +/+ and p16 +/LUC animals (Figure S2K).…”
Section: Resultssupporting
confidence: 86%
“…Figs. [6][7][8]. Based on these findings, the frequency of epithelial hyalinosis affecting extrapulmonary sites was significantly higher in 129S6/SvEvTac females than males.…”
Section: Spectrum Of Nonneoplastic Lesionsmentioning
confidence: 71%
“…151,156 Hematopoietic tumors were the primary cause of death in 4WC mice and found in 55% of male and 43% of female mice when pathology was evaluated. 53 Frequency of tumors (or of other pathology phenotypes) has been defined as the proportion of mice with tumors in animals submitted for necropsy. The data may be skewed if some strains are maintained and studied to later ages than others (eg, aging nulliparous research populations vs younger breeding populations).…”
Section: Experimental Designmentioning
confidence: 99%